Factors Associated with Respiratory Insufficiency in Children with Guillain–Barré Syndrome - Sun, Rui-di; Jiang, Jun; Deng, Xiao-long (Neuropediatrics, 2024)
Objective The risk factors for respiratory insufficiency in children with Guillain–Barré syndrome (GBS) are poorly known. This study aimed to investigate the factors associated with respiratory insufficiency in children with GBS.Methods This retrospective study included children diagnosed with GBS by pediatric neurologists and admitted at the Wuhan Children's Hospital and other hospitals from January 2013 to October 2022. The patients were divided into the respiratory insufficiency and nonrespiratory insufficiency groups according to whether they received assist breathing during treatment.Results The median (interquartile range) age of onset of 103 patients were 5 (3.1–8.5) years, 69 (67%) were male, and 64 (62.1%) had a history of precursor infection. Compared with the nonrespiratory insufficiency group, the respiratory insufficiency group showed more facial and/or bulbar weakness (p = 0.002), a higher Hughes Functional Grading Scale (HFGS) at admission (p < 0.001), and a shorter onset-to-admission interval (p = 0.017). Compared with the acute motor axonal neuropathy (AMAN) subtype, the acute inflammatory demyelinating polyneuropathy (AIDP) subtype showed longer days from onset to lumbar (p = 0.000), lower HFGS at admission (p = 0.04), longer onset-to-admission interval (p = 0.001), and more cranial nerve involvement (p = 0.04). The incidence of respiratory insufficiency between AIDP and AMAN showed no statistical difference (p > 0.05).Conclusion In conclusion, facial and/or bulbar weakness, HFGS at admission, and onset-to-admission interval were associated with respiratory insufficiency and might be useful prognostic markers in children with GBS.
Keywords: Guillain–Barré syndrome; respiratory insufficiency; prognosis; muscle weakness; physical functional performance; cerebrospinal fluid